Effectiveness, efficiency and adverse effects of using direct or indirect bonding technique in orthodontic patients: a systematic review and meta-analysis - Yanxi Li; Li Mei; Jieya Wei; Xinyu Yan; Xu Zhang; Wei Zheng; Yu Li (BMC, 2019)
Abstract Background The direct and indirect bonding techniques are commonly used in orthodontic treatment. The differences of the two techniques deserve evidence-based study. Materials and methods Randomized controlled trials (RCTs), wherein direct and indirect bonding techniques were used in orthodontic patients were considered. The MEDLINE, EMBASE, CENTRAL and Web of Science databases were searched to identify relevant articles published up to December 2018. Grey literature was also searched. Two authors performed data extraction independently and in duplicate using the data collection form. The included trials were assessed using the Cochrane risk of bias assessment tool. Results Of the 1557 studies screened, 42 full articles were scrutinized and assessed for eligibility. Eight RCTs (247 participants) were finally included for the analyses. The qualitative synthesis showed that no significant difference existed in the accuracy of bracket placement and oral hygiene status between the two bonding techniques. The indirect bonding was found to involve less chairside time but more total working time compared with the direct bonding. The meta-analysis on bond failure rate demonstrated no significant difference between the direct and indirect bonding (RR = 1.13, 95% CI = 0.78-1.64, I2 = 22%, P = 0.50). Consistent results were obtained in the subgroup analyses and sensitivity analyses. Conclusion Weak evidence suggested that the direct and indirect bonding techniques had no significant difference in bracket placement accuracy, oral hygiene status and bond failure rate, for bonding orthodontic brackets. The indirect bonding might require less chairside time but more total working time in comparison with the direct bonding technique. High-quality well-designed randomized controlled trials are needed before a conclusive recommendation could be made.